Great Barrier Reef No‐Take Areas Include a Range of Disturbance Regimes. Issue 3 (28th September 2015) - Maynard, Jeffrey A.; Beeden, Roger; Puotinen, Marjetta; Johnson, Johanna E.; Marshall, Paul; van Hooidonk, Ruben; Heron, Scott F.; Devlin, Michelle; Lawrey, Eric; Dryden, Jen; Ban, Natalie; Wachenfeld, David; et al.
Abstract: Exposure to disturbance is rarely considered in marine protected area planning. Typically, representing and replicating the habitat types present within protected areas is used to spread the risk of protecting frequently disturbed sites. This was the approach used during the 2004 re‐zoning of the Great Barrier Reef Marine Park (GBRMP) via the Representative Areas Program. Over 10 years later, we examine whether the risk was spread by mapping exposure of coral reefs in the GBRMP to four disturbances that cause coral mortality: bleaching, tropical cyclones, crown‐of‐thorns starfish outbreaks, and freshwater inundation. Our objectives were to: (1) assess whether no‐take areas include a range of disturbance regimes, and (2) identify coral reef areas with lower relative exposure. At least 13% and an average of 31% of reef locations in each of 11 exposure classes are included within no‐take areas. A greater proportion of low‐exposure areas are within no‐take areas than high‐exposure areas (34.2% vs. 28.3%). The results demonstrate the value of risk spreading when exposure data are not available while also showing that regularly assessing exposure increases capacity for adaptive, resilience‐based reef management.